Photodynamic Therapy Efficacy of Novel Zinc Phthalocyanine Tetra Sodium 2-Mercaptoacetate Combined with Cannabidiol on Metastatic Melanoma - Nkune Williams Nkune; Gauta Gold Matlou; Heidi Abrahamse (MDPI AG, 2022)
This work reports for the first time on the synthesis, characterization, and photodynamic therapy effect of a novel water-soluble zinc (II) 2(3), 9(10), 16(17), 23(24)-tetrakis-(sodium 2-mercaptoacetate) phthalocyanine (ZnPcTS41), on metastatic melanoma cells (A375) combined with cannabidiol (CBD). The ZnPcTS41 structure was confirmed using FTIR, NMR, MS, and elemental analysis while the electronic absorption spectrum was studied using UV-VIS. The study reports further on the dose-dependent effects of ZnPcTS41 (1-8 µM) and CBD alone (0.3-1.1 µM) at 636 nm with 10 J/cm2 on cellular morphology and viability. The IC50 concentrations of ZnPcTS41 and CBD were found to be 5.3 µM and 0.63 µM, respectively. The cytotoxicity effects of the ZnPcTS41 enhanced with CBD on A375 cells were assessed using MTT cell viability assay, ATP cellular proliferation and inverted light microscopy. Cell death induction was also determined via Annexin V-FITC-PI. The combination of CBD- and ZnPcTS41-mediated PDT resulted in a significant reduction in cell viability (15%***) and an increase in the late apoptotic cell population (25%*). These findings suggest that enhancing PDT with anticancer agents such as CBD could possibly obliterate cancer cells and inhibit tumor recurrence.